The (re)definition of Hospitals in Portuguese welfare system. An international and conceptual debate during the nineteenth century. - Silva, Daniela (ESSHC - European Social Science History Conference, Valencia 2016, 2016)
Abstract The states and their welfare and health care systems take effect in the mind-sets about behaviour and conceptions towards the poor, the sick and the pauper, as well as in the reformation of practices and ideals towards the institutes that are meant to interact with them. However, it’s also an influence that can or cannot be in agreement with other kind of power: medicine and scientifical knowledge. Thus the public policies about social welfare, health care and poor relief are revised, redraft and envisioned by the medical professional class, as legitimated agents and actors of the nation’s social control structures in the nineteenth century. This professional class, whom were called by the governments to scientifically certify political measures regarding medical police control, as well as administrative, legal and public health issues, acquired, by capitalizing the State’s legitimacy in those matters, a position of professional responsibility to interfere in other questions, that, in spite of concerning to poor relief and health care, were confined and limited to the political governance action. Hospital buildings and constructions, administration, practices and functions, were brought to their agendas and broadly debated, interfering with the State´s political action and economic and social concerns, quite different from theirs. While some medical statements required the extinction of hospitals by their hopelessness, others found that clinical science could in fact save them and turn them into useful and beneficial institutions for medical care. The Portuguese hospital scenario comes with a singular framework regarding international realities by their structure and nature. Since the fifteenth century, poor relief and health care were strictly controlled and mandate by the State´s jurisdiction, preformed by a network of institutions all over Portuguese territory, ruled by one standard program and out of reach to any Ecclesial authority interference. However, these institutions were founded and sustained upon the Christian charity axiom, as their practices and representations towards poor relief and hospitals. Therefore, this mind-set circumstance, adversely constrained the process of hospitals reforms, proclaimed and settled by medical science, regarding to the paramount principles of the how’s and why’s in their clinical conceptions permanently over the century. The questions to be raised by this paper are, as well, how and why the international debate towards reconceptualising hospitals - through the media dialogue, treaties and associative scientific discussions accounts - were chosen by Portuguese medical class, using them as stimulation by the similarity of problem recognition in one way, and, as resolutions in another by experimented successes. Through the use of Conceptual History methods it is possible to identify as well, correlations between these State’s welfare policies and their own hospital care representations. Foucault’s Birth of the Clinic provided also the guidelines to offer a comparative scenario between nation’s welfare policies and their own medical class assertions and claims, in the conceptual understanding of two different kind of authorities: the Political and the Medical one.